2020
DOI: 10.2174/1573397116666200312142709
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width (RDW) as a Marker of Subclinical Inflammation in Children with Familial Mediterranean Fever

Abstract: Aims: To probe whether RDW can be used as a reliable indicator of subclinical disease in FMF patients. Background: Familial Mediterranean fever (FMF) is an auto inflammatory disease with potentially devastating effects on the kidney, and the chronic subclinical inflammation may also be deleterious. Further, proteinuria has been associated with chronic inflammatory states. Objective: To probe whether RDW can be used as a reliable indicator of subclinical disease in FMF patients. Method: Ninety-nine ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…It is critical to determine SI with simple, inexpensive and easy methods compared to the analysis of inflammatory cytokines mentioned above. Therefore, to date, some new inflammatory markers have been investigated in the evaluation of SI in FMF [1,3,23,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is critical to determine SI with simple, inexpensive and easy methods compared to the analysis of inflammatory cytokines mentioned above. Therefore, to date, some new inflammatory markers have been investigated in the evaluation of SI in FMF [1,3,23,27].…”
Section: Discussionmentioning
confidence: 99%
“…We also revealed that MPV was not associated with SI in our patients with FMF. Marzouk et al [23] concluded that RDW was a reliable marker for SI. Özer et al [27] reported that the PLR levels could be used to assess SI in FMF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the relationship between RDW and the occurrence of PE in COPD patients is a relatively uninvestigated area. RDW is associated with several inflammatory markers, such as acute-phase reactants C-reactive protein (CRP), erythrocyte sedimentation rate, and platelet count [ 18 , 19 ]. Studies have shown that markers of systemic inflammation, such as CRP, IL-6, IL-8, and TNF- α , contribute to the development of thrombotic events [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, subclinical inflammation (SI) may progress during attack-free intervals in FMF and triggers amyloidosis despite colchicine therapy [10,11]. Recently, inflammation during the symptom-free periods of FMF has been reported to correlate with simple inflammatory-based scores, including the mean platelet volume (MPV), red cell width distribution (RDW), neutrophil/lymphocyte ratio (NLR), and platelet/lymphocyte ratio (PLR) [12][13][14][15][16]. The CRP/serum albumin ratio (CAR) is a new inflammation score used as a marker of chronic inflammation and prognosis in solid tumours [17], critically ill patients [18], rheumatoid arthritis [19], and ANCA-associated vasculitis [20].…”
Section: Introductionmentioning
confidence: 99%